Becoming a Problem Based Learning Facilitator : 2 Mistakes to Avoid - Lim, William/W.K. (YouTube, 2020)
Problem Based Learning (PBL) is a student-centred pedagogic approach developed at McMaster University over 50 years ago. It is used in diverse disciplines and levels and remains a 21st century Transformative Learning and Teaching Delivery in Higher Education 4.0. But when the Facilitators/Tutors and curriculum planners have a teacher-centred learning philosophy, there are often problems in its implementation due to incompatible educational philosophies. This video highlights two common problems with PBL facilitators who are used to teacher-centred learning practices. The first is they may give mini lectures in the PBL room. The second is (if they are required to grade the students) they focus on ensuring quieter students receive a lower grade. Hence firstly they should not assume that knowledge can be transmitted by lecturing, but support student-led knowledge construction. Secondly they need to support student learning by helping the quieter ones to improve, even if it means having to converse personally. They must be facilitators of learning who help students become effective lifelong learners.